Development of solar powered screen cleaner - ARADWAD, PRAMOD P; SINHA, J P; T V, ARUNx T V; YADAV, RAHUL S; SAMUEL, D V K (The Indian Journal of Agricultural Sciences, 2018)
Harvested grain mass contains various impurities that need to be removed before further processing. A solar powered screen cleaner was designed, fabricated and tested for separating impurities from soybean, lentil and chickpea grains. The machine consists of frame, feeding chute, screen cradle, discharge outlets, and drive unit. The angle of tilt of the sieve was varied between 3 and 8° while the hanger angle was maintained at 5°. Operating parameters such as screen cradle angle, oscillation and feed rate were optimized and the optimum performance was achieved at a screen cradle angle of 50, screen oscillation of 3.6 Hz, and feed rate of 150 kg/h.The slope of the sieve unit, cradle speed and stroke length could be adjusted easily. The developed unit was evaluated with 5 kg sample consisting of 80%, 85%, and 90% pure hand-cleaned grains mixed with 20%,15% and 10% impurities (chaff, stem, other crop seeds, weed seeds, clods, stones, etc.). The cleaning efficiency for whole chickpea, soybean and lentil was found to be 88.27%, 87.14% and 84.3%, respectively, and the losses observed was 2.12%, 1.25% and 1.73%, respectively. Overall machine efficiency was observed to be 83%.This machine assures good quality grain at affordable energycost to small and marginal farmers in rural India.